Hematoma of the Flexor Tendon Sheath Mimicking Acute Septic Tenosynovitis: A Case Report. Issue 3 (July 2016) - Slaughter, Jonathan B.; Pulos, Nicholas; Lim, Daniel P.; Bozentka, David J.
Abstract : Case: We report a case of a 65-year-old woman receiving chronic anticoagulation who presented with acute onset of severe long finger pain and was supratherapeutic on Coumadin. Her examination was consistent with early septic flexor tenosynovitis. She was treated with antibiotics and tendon sheath incision and drainage. Intraoperatively, she was found to have a hematoma in the flexor tendon sheath with no purulence. Her symptoms resolved with decompression. After 2 months, she had regained full range of motion with no deficits. Conclusion: Flexor tendon sheath hematoma warrants consideration in the differential diagnosis of patients presenting with the signs and symptoms of acute septic flexor tenosynovitis.